Cytotoxicity Effect of Quercus infectoria Based Vaginal Cream on Hela Cells and its Preliminary in Vivo Toxicity Evaluation Towards Female Rats - MY, Hazwani; A, Hasmah; Nizam WA, Wan Amir (IIUM Medical Journal Malaysia, 2020)
Introduction: Cervical cancer is the third leading cause of cancer death among females in less developed countries. Drugs used in the treatment of cervical cancer were reported to exert a cytotoxic effect on the normal cells. This study aimed to determine the effectiveness of Quercus infectoria (QI) vaginal cream towards cervical cancer cell, HeLa and its toxicity effect on the female rat model. Methods: MTT assays were utilized to determine the median concentration (IC50) for cell cytotoxicity of QIA and QI vaginal cream against cervical cancer cells, HeLa. Expression of HPV E6 and E7 protein in HeLa cells treated with QI vaginal cream for 24 hours were conducted by Western blot analysis. In separate experiments, the toxicity of QI vaginal cream on a lower reproductive tract of the female rat model has been assessed by histopathological examination after application for three weeks. The antioxidant activity of QIA extract and QI vaginal cream were assessed by DPPH radical scavenging assay. Results: A moderate cytotoxicity activity exerted by QIA extract and QI vaginal cream against HeLa cell with IC50 values of 13.90 ± 2.27, and 20.80 ± 1.94 respectively. Furthermore, QI vaginal cream suppressed the expression of HPV E6 and E7. Daily application of QI vaginal did not exert any inflammation to the vaginal mucosa and cervix. QIA extract and QI vaginal cream demonstrated high DPPH radical scavenging activity. Conclusion: Formulated QI vaginal cream has cytotoxic effect on HeLa cells without causing an adverse effect on the lower reproductive tract in female rat model.